2019
DOI: 10.1038/s41398-019-0474-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin receptors in the dorsolateral bed nucleus of the stria terminalis (BNST) bias fear learning toward temporally predictable cued fear

Abstract: The inability to discriminate between threat and safety is a hallmark of stress-induced psychiatric disorders, including post-traumatic stress disorder. Dorsolateral bed nucleus of the stria terminalis (BNST dl ) is critically involved in the modulation of fear and anxiety, and has been proposed to regulate discrimination between signaled (cued, predictable) and unsignaled (unpredictable) threats. We recently showed that oxytocin receptors (OTRs) in the BNST dl fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…These results indicate that OTR neurotransmission in the BNST DL facilitates the acquisition of fear to a discrete cue. We later confirmed the recruitment of endogenous OT in the acquisition of cued fear memory with a microdialysis study showing that cued-fear conditioning indeed evokes OT release in the BNST DL (Martinon et al, 2019).…”
Section: The Bed Nucleus Of the Stria Terminalissupporting
confidence: 60%
See 4 more Smart Citations
“…These results indicate that OTR neurotransmission in the BNST DL facilitates the acquisition of fear to a discrete cue. We later confirmed the recruitment of endogenous OT in the acquisition of cued fear memory with a microdialysis study showing that cued-fear conditioning indeed evokes OT release in the BNST DL (Martinon et al, 2019).…”
Section: The Bed Nucleus Of the Stria Terminalissupporting
confidence: 60%
“…We have recently shown that cued and contextual fear conditioning activate hypothalamic neurons differently, such that contextual fear conditioning (un-signaled foot-shocks) activates OT neurons in the PVN, SON, and AN, whereas cued fear conditioning (foot-shocks signaled by a cue) activates OT neurons in the SON and AN, but not the PVN of male rats. Overall, contextual fear conditioning caused more robust activation of OT neurons than cued fear conditioning in all three hypothalamic nuclei, suggesting that OT neurons are activated more in the conditions of uncertainty (Martinon et al, 2019). Previously, contextual fear conditioning was shown to activate magnocellular OT neurons in the PVN and SON of male rats (Zhu and Onaka, 2002).…”
Section: The Involvement Of Endogenous Oxytocin System In the Modulatmentioning
confidence: 76%
See 3 more Smart Citations